Future-Oriented Civil and Private Law: Integrating Artificial Intelligence (AI) and Machine Learning (ML) Technologies - Alawamleh Atef Salem (Central European Journal of Public Policy)
A recent study delved into the burgeoning fields of artificial intelligence (AI) and machine learning (ML) within civil and private law. The study, which focused on analyzing 140 academic papers published from 2017 to 2023 using software tools such as RStudio, VOSviewer, and Excel, revealed a significant rise in publications, particularly since 2020. Key research topics have examined the application of AI in decision-making on civil and private law, argument, persuasion and progress in the legal processing of natural language through deep learning techniques. The study also identified leading contributions from scientists in the US, Canada and the Netherlands. However, it also recognizes the need for further research to evaluate the effectiveness of various AI and ml methodologies in legal contexts. This in turn would support civil and private evidence-based rights in various sectors and geographical regions, which would increase their usability and integration.